2012
DOI: 10.17310/ntj.2012.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Tax Preferences for Higher Education and Adult College Enrollment

Abstract: The federal government delivers substantial college aid through the tax code, after introducing education tax credits in 1998 and a tuition deduction in 2002. The design of the Lifetime Learning tax credit and the tuition deduction may make them particularly useful to older students. This paper investigates how these provisions have affected college attendance of individuals in their 30s and 40s. For most adults, there is no effect on college attendance. Among men whose 1998 educational attainment falls short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…2 As tax benefits for college have grown, several studies have considered their effect on student outcomes. These studies have generally found that they did not affect college enrollment (Bulman & Hoxby, 2015;Hoxby & Bulman, 2016;LaLumia, 2012;Long, 2004). A notable exception is Turner (2011a), who found an increase in enrollment with tax aid generosity using changes in benefit generosity over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 As tax benefits for college have grown, several studies have considered their effect on student outcomes. These studies have generally found that they did not affect college enrollment (Bulman & Hoxby, 2015;Hoxby & Bulman, 2016;LaLumia, 2012;Long, 2004). A notable exception is Turner (2011a), who found an increase in enrollment with tax aid generosity using changes in benefit generosity over time.…”
Section: Introductionmentioning
confidence: 99%
“…However, for individual students, the information sent in this study is still relevant because they will receive less tax aid if they do not claim the benefits. LaLumia () focuses on older students using a person‐fixed effect approach and finds no effects for the sample as a whole, but positive effects for some subsamples.…”
mentioning
confidence: 99%
“…In contrast, the tax relief measures do not appear to affect part-time enrolment in the first two years of college. Among adults aged 33 to 41, Lalumia (2010) found that eligibility for one of these three tax provisions increased the probability of college enrolment for people whose educational attainment expectations as teenagers had not been previously met.…”
Section: United Statesmentioning
confidence: 99%
“…This points to the importance of public awareness and ease of compliance to ensure effective take-up of tax relief for the costs of education. In spite of these issues, there is also evidence that tax relief can ultimately have a positive impact on enrolment (Lalumia, 2010;Turner, 2011a). Overall, more research is needed in OECD countries to empirically evaluate the impact of personal tax relief on human capital investments, particularly regarding lifelong learning financed by individuals where no evidence is available.…”
Section: Deductibility Of Education and Training Costsmentioning
confidence: 99%
“…Similarly, short-term loans covering tuition fees in South African public universities were estimated to double enrollment rates of admitted disadvantaged students (Gurgand, Lorenceau, & Mélonio, 2011). In contrast, the available evidence on tax incentives does not suggest any positive impact for disadvantaged groups' access to higher education (Table C.6 in Appendix C) as two studies in the U.S. fail to identify an effect on enrollment for disadvantaged students (Bulman & Hoxby, 2015;LaLumia, 2012) As these tax incentives only provide income relief about 10.5 months after enrollment, these may not be very effective in addressing unmet financial need. Moreover, these tax incentives tend to benefit middle-and upper-income families, as lowest-income families do not pay taxes and are thus not eligible for them.…”
mentioning
confidence: 99%